2019
DOI: 10.1002/jssc.201801093
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive separation of methylprednisolone acetate using a photoresponsive molecularly imprinted polymer incorporated polyester dendrimer based on magnetic nanoparticles

Abstract: We developed an approach for the use of polyester dendrimer during the imprinting process to raise the number of recognized sites in the polymer matrix and improve its identification ability. Photoresponsive molecularly imprinted polymers were synthesized on modified magnetic nanoparticles involving polyester dendrimer which uses the reactivity between allyl glycidyl ether and acrylic acid for the high‐yielding assembly by surface polymerization. The photoresponsive molecularly imprinted polymers were construc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…On the other hand, smart materials that can respond in their structure and polarity by altering external stimuli (temperature, pH, ionic strength, etc.) have garnered tremendous attention as stationary phases [39][40][41][42][43][44][45][46][47][48]. This type of material allows stimuli-sensitive recognition of proteins which is very similar to the recognition in natural systems [49,50].…”
Section: Protein Imprintingmentioning
confidence: 99%
“…On the other hand, smart materials that can respond in their structure and polarity by altering external stimuli (temperature, pH, ionic strength, etc.) have garnered tremendous attention as stationary phases [39][40][41][42][43][44][45][46][47][48]. This type of material allows stimuli-sensitive recognition of proteins which is very similar to the recognition in natural systems [49,50].…”
Section: Protein Imprintingmentioning
confidence: 99%
“…The effect of contact time of IM onto the β-CD @Fe 3 O 4 NP s /GPTMS at different contact time (2,5,10,20,30,45,60, 90 and 120 min) are shown in Figure S5. The maximum adsorption efficiency of 100% was observed at the contact time of 30 min while the other factors were temperature 25°C, pH = 5, and adsorbent dosage 0.015 g. It can be observed that the adsorption efficiency of β-CD @Fe 3 O 4 NP s /GPTMS for IM was significantly increased during the first 30 min, after which it remained almost constant.…”
Section: Effect Of Contact Timementioning
confidence: 99%
“…Magnetic nanoparticles (MNPs) can be used in the field of medical [4,5], environmental [6][7][8], and chemical engineering [9,10]. Recently, MNPs as drug delivery systems have attracted an enormous attention.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular imprinting is a procedure which forms recognition locations that are very specific for the unique target molecule, called a template, within a synthetic polymer, and it has been used for the selective adsorption of drugs with great result and their metabolites for analytical goals [26][27][28][29]. The process of molecularly imprinted polymer procedure is to involve the formation of complex in solution of a template by help of functional monomer via non-covalent or covalent interactions, through the polymerization of these monomers around the template in the presence of a radical initiator a cross-linker, and suitable solvent [30].…”
Section: Introductionmentioning
confidence: 99%